Strengthening Maternal and Child Health Literacy through Community Service Programs - Komang Widhya Sedana Putra P; Wayan Sri Maitri; Ni Wayan Lasmi (Eastasouth Journal of Positive Community Services, 2026)
Maternal and child health literacy plays a vital role in improving family well-being and community resilience. However, limited access to accurate health information remains a major challenge in many communities. This community service program aimed to strengthen maternal and child health literacy through participatory education and basic health services in Padangsambian Klod Village, Denpasar. The program was implemented on February 5, 2026, using an interactive approach that combined health education sessions, individual counseling, and basic health examinations. Data were collected through observation, participant feedback, and informal interviews to evaluate program effectiveness. The results showed significant improvements in participants’ understanding of maternal nutrition, child growth monitoring, hygiene practices, immunization awareness, and health-seeking behavior. Participants also demonstrated increased confidence in managing family health and greater willingness to access professional healthcare services. The integration of culturally sensitive communication and practical demonstrations contributed to high community engagement and knowledge retention. This program proves that community-based health literacy initiatives can effectively enhance maternal and child health awareness. Sustainable implementation and continuous evaluation are recommended to ensure long-term impact. The findings provide practical insights for developing community empowerment models in public health services.